Oncologic outcomes with and without amniotic membranes in robotic-assisted radical prostatectomy: A propensity score matched analysis - Jonathan Noël; Daniel Stirt; Marcio Covas Moschovas; Sunil Reddy; Abdel Rahman Jaber; Marco Sandri; Seetharam Bhat; Travis Rogers; Subuhee Ahmed; Anya Mascarenhas; Ela Patel; Vipul Patel (Asian Journal of Urology)
Objective: Placement of human placenta derived grafts during robotic-assisted radical prostatectomy (RARP) hastens the return of continence and potency. The long-term impact on the oncologic outcomes remains to be investigated. Our objective was to determine the oncologic outcomes of patients with dehydrated human amnion chorion membrane (dHACM) at RARP compared to a matched cohort. Methods: In a referral centre, from August 2013 to October 2019, 599 patients used dHACM in bilateral nerve-sparing RARP. We excluded patients with less than 12 months follow-up, simple prostatectomy, and unilateral nerve-sparing. Patients with dHACM (amnio group) were 529, and were propensity score matched 1:1 to 2465 patients without dHACM (non-amnio group) and a minimum follow-up of 36 months. At the time of RARP, dHACM was placed around the neurovascular bundle in the amnio group. Continuous and categorical variables in matched groups was tested by two-sample Kolmogorov-Smirnov test and Fisher's exact test respectively. Outcomes measured were biochemical recurrence (BCR), adjuvant and salvage therapy rates. Results: Propensity score matching resulted in two groups of 444 patients. Cumulative incidence functions for BCR did not show a difference between the groups (p=0.3). Patients in the non-amnio group required salvage therapy more frequently than the amnio group, particularly after partial nerve-sparing RARP (6.3% vs. 2.3%, p=0.001). Limitations are the absence of prospective randomization. Conclusion: The data suggest that using dHACM does not have a negative impact on BCR in patients. Outcomes of cancer specific and overall survival will require follow-up study to increase our understanding of these grafts’ impact on prostate cancer biology.